Systematics and biogeography of tube-nosed bats, Murina (Mammalia, Chiroptera, Vespertilionidae), from the Philippines with descriptions of six new species - Eger, Judith L.; Sedlock, Jodi L.; Lim, Burton K.; Heaney, Lawrence R. (Zootaxa, 2025)
Murina is a wide-ranging genus of insectivorous bats that occurs throughout Asia whose known diversity has recently been increasing with the description of 26 new species in the past 20 years. The Philippine archipelago—mostly comprised of islands with oceanic origin and thus a history of isolation—has produced a fauna rich in endemic species, including bats. Here, we describe the morphological and genetic diversity among Murina specimens collected from across the Philippine islands and compare them to representatives from the Southeast Asian mainland and adjacent islands. Our results show that the wide-spread M. cyclotis represents a radiation, beginning around 11 mya, of five distinct Murina species endemic to the Philippines, including three single-island endemics. These five new M. cyclotis group species are mostly allopatric in distribution, except for two species—the smallest and largest that occur in the Philippines—that co-occur on Mindanao Island. Our study documents Murina suilla, a species occurring in Indonesia, Malaysia and Thailand, and only occurring on Mindoro and Palawan Islands within the Philippines. Additionally, we describe a new species that is sister to M. suilla and is widespread across the Philippine archipelago. Overall, our study has increased the number of Philippine Murina species from two to seven. As the first phylogeographic analysis of a laryngeal echolocating bat genus within the Philippines, our study provides evidence that the diversification of understory insectivorous bats largely echoes that of fruit bats (Pteropodidae), which is characterized by endemic Philippine lineages that are primarily confined to known biogeographic regions that constitute sets of modern islands that were connected during the last ice age, or to individual oceanic islands. We hypothesize that subsequent phylogeographic investigations of other bat taxa may reveal similar, previously unrecognized, endemic radiations within the highly biodiverse Philippines.